Flooded pasts: UNESCO, Nubia, and the recolonization of archaeology - Carruthers, William (Cornell University Press, 2022)
Introduction: Flooding Nubia -- The view from the boat -- Documenting Nubia -- Valuing Egyptian Nubia -- Making Sudan archaeological -- Peopling Nubia -- Nubia in the (non-aligned) world -- Traces of Nubia -- Conclusion: Repeopling Nubia.